A Unique Test Bench for Various System-on-a-Chip - Sridevi Chitti; P. Chandrasekhar; M. Asharani (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper discusses a standard flow on how an automated test bench environment which is randomized with constraints can verify a SOC efficiently for its functionality and coverage. Today, in the time of multimillion gate ASICs, reusable intellectual property (IP), and system-on-a-chip (SoC) designs, verification consumes about 70 % of the design effort. Automation means a machine completes a task autonomously, quicker and with predictable results. Automation requires standard processes with well-defined inputs and outputs. By using this efficient methodology it is possible to provide a general purpose automation solution for verification, given today’s technology. Tools automating various portions of the verification process are being introduced. Here, we have Communication based SOC The content of the paper discusses about the methodology used to verify such a SOC-based environment. Cadence Efficient Verification Methodology libraries are explored for the solution of this problem. We can take this as a state of art approach in verifying SOC environments. The goal of this paper is to emphasize the unique testbench for different SOC using Efficient Verification Constructs implemented in system verilog for SOC verification.